LEGAL PROTECTION FOR HEIRS REGARDING INHERITANCE OF LAND OWNERSHIP RIGHTS THAT HAVE NOT BEEN REGISTERED AT THE JAYAPURA REGENCY LAND OFFICE - Solossa, Marthinus; Yoseph Palenewen, James; Tanati, Daniel (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The research, entitled "Legal Protection for Heirs of Land Ownership Rights Not Registered at the Jayapura Regency Land Office," aims to determine the legal consequences of land ownership transfers due to unregistered inheritances at the Jayapura Regency Land Office and to determine the legal protection for heirs of unregistered inheritances. The methods used in this research are normative and empirical juridical. Normative juridical refers to an approach that refers to laws, literature, written regulations, or other secondary legal materials. Empirical juridical identifies and conceptualizes law as a real and functional social institution within the real-life system. The output of this research is to contribute legal thought and knowledge to the National Land Agency (BPN) and the community in Jayapura Regency regarding the importance of land ownership transfers due to inheritance to ensure legal certainty and orderly land law administration.